Adverse event associated with auriculotherapy. Issue 1 (10th January 2017) - Morita, Akira; Shimada, Hirobumi; Yagi, Akio; Nagamine, Koichi; Nagai, Chigusa; Ryu, Koichi; Takano, Shizuko; Okamoto, Hideki; Hirasaki, Yoshiro; Namiki, Takao
ABSTRACT: Case: A 76‐year‐old man with tympanic membrane perforation and hearing loss in the right ear since childhood was hospitalized in September 2015 due to deterioration of renal function. On cranial magnetic resonance imaging (MRI) to evaluate possible cerebrovascular disorder, an artifact was observed. Further, cranial computed tomography (CT) showed seven metallic objects in the region extending from the right external ear canal to the right middle ear. Outcome: The objects were determined to be acupressure pellets measuring 1 mm in diameter. Conclusion: Taking careful history of any prior ear disease is essential, as is the conducting of thorough examination for tympanic membrane perforation. Use of acupressure pellets on the anterior auricle should be avoided in patients with tympanic membrane perforation.